Precession electron diffraction tomography on twinned crystals: application to CaTiO3 thin films. Issue 3 (31st May 2019) - Steciuk, Gwladys; David, Adrian; Petříček, Václav; Palatinus, Lukáš; Mercey, Bernard; Prellier, Wilfrid; Pautrat, Alain; Boullay, Philippe
Abstract : Electron diffraction is used to obtain accurate structural parameters from thin films by taking into account the presence of twinning. Abstract : Strain engineering via epitaxial thin‐film synthesis is an efficient way to modify the crystal structure of a material in order to induce new features or improve existing properties. One of the challenges in this approach is to quantify structural changes occurring in these films. While X‐ray diffraction is the most widely used technique for obtaining accurate structural information from bulk materials, severe limitations appear in the case of epitaxial thin films. This past decade, precession electron diffraction tomography has emerged as a relevant technique for the structural characterization of nano‐sized materials. While its usefulness has already been demonstrated for solving the unknown structure of materials deposited in the form of thin films, the frequent existence of orientation variants within the film introduces a severe bias in the structure refinement, even when using the dynamical diffraction theory to calculate diffracted intensities. This is illustrated here using CaTiO3 films deposited on SrTiO3 substrates as a case study. By taking into account twinning in the structural analysis, it is shown that the structure of the CaTiO3 films can be refined with an accuracy comparable to that obtained by dynamical refinement from non‐twinned data. The introduction of the possibility to handle twin data sets is undoubtedly a valuable add‐on and, notably, paves the way for a successful use of precession electron diffraction tomography for accurate structural analyses of thin films.